Cellular response of pulp fibroblast to single or multiple photobiomodulation applications. (3rd May 2018) - Fernandes, Amanda; Neto, Natalino Lourenço; Marques, Nadia Carolina Teixeira; Vitor, Luciana Lourenço Ribeiro; Prado, Mariel Tavares Oliveira; Oliveira, Rodrigo Cardoso; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini
Abstract: This study aimed to evaluate in vitro the effects of single or multiple photobiomodulation (PBM) applications on the viability and proliferation of pulp fibroblasts. Pulp fibroblasts from human deciduous teeth were obtained from a biorepository, plated into 96-well plates, and irradiated according to the experimental groups. At 24 h, 48 h, and 72 h after irradiation, cell viability and proliferation were assessed through MTT and Crystal Violet assays, respectively. The intragroup comparison revealed statistically significant differences for 2.5 J cm −2 (3×) with increasing viability at 72 h over 48 h (p = 0.027). The intergroup analysis showed a greater viability of the multiple PBM applications 2.5 J cm −2 (3×) over the single application 7.5 J cm −2 (1×) at 72 h. The application of 5 J cm −2 (1×) exhibited greater proliferation than the application of 7.5 J cm −2 (1×), 2.5 J cm −2 (2×) and 2.5 J cm −2 (3×). Single or multiple PBM applications demonstration different stimulatory effects on pulp fibroblast. The results show that the group submitted to multiple irradiation presented significantly higher cell viability than the groups with single irradiation at 72 h. However, the photobiomodulation therapy with single irradiations was more effective on cell proliferation at 24 h.